Chromium supplementation for adjuvant treatment of type 2 diabetes mellitus: Results from a pooled analysis. Issue 1 (15th August 2017) - Huang, Haohai; Chen, Guangzhao; Dong, Yong; Zhu, Yongkun; Chen, Honglang
Abstract : Scope: We conducted a pooled analysis of randomized controlled trials to evaluate the effects of chromium supplementation on clinically relevant metabolic biomarkers in type 2 diabetes mellitus (T2DM) patients. Methods and results: Electronic searches were conducted and the bibliographies of located articles were searched, and 28 studies were suitable for statistical pooling. Endpoints were calculated as weighted mean differences (WMDs) with 95% confidence intervals (CIs) by using fixed‐effects or random‐effects models. Statistical heterogeneity, publication bias, subgroup analyses, sensitivity analysis and meta‐regression assessments were also assessed. Chromium reduced levels of fasting plasma glucose (WMD, −0.99 mmol/L; 95% CI, −1.72 to −0.25; p = 0.008), hemoglobin A1c (WMD, −0.54 %; 95% CI, −0.82 to −0.25; p = 0.0002), triglycerides (WMD, −11.71 mg/dL; 95% CI, −18.38 to −5.04; p = 0.0006). Chromium also increased levels of high‐density lipoprotein cholesterol (WMD, 1.73 mg/dL; 95% CI, 0.50 to 2.96; p = 0.006). These results were robust in sensitivity analysis and were not dependent on the chromium dose and duration of supplementation. Subgroup analyses indicated that these notably favorable effects were presented in T2DM subjects ingesting chromium chloride and chromium picolinate formulations. Conclusion: Our pooled analysis suggested that chromium supplementation might be a candidate as an adjunct to pharmacological management in patients with T2DM. Abstract : The present finding provides evidence that T2DM patient consumption of chromium is associated with a statistically significant decrease in levels of fasting plasma glucose, hemoglobin A1c, triglycerides, and an increase in high‐density lipoprotein cholesterol levels. Chromium is thus a potential therapeutic strategy that could prevent and improve the management of patients with T2DM. These results were robust in sensitivity analysis and were not dependent on the chromium dose and duration of supplementation. Subgroup analyses indicated that these notably favorable effects were presented in T2DM subjects ingesting chromium chloride and chromium picolinate formulations. No significant publication bias was detected and no serious adverse events (AEs) occurred among most of the eligible trials during the study period.